Estudo de genômica comparativa de corynebacterium pseudotuberculosis linhagem 226 (biovar ovis) - DIAS, Larissa Maranhão (Universidade Federal do Pará, 2015)
Corynebacterium pseudotuberculosis is a gram-positive, facultative intracellular, non-sporulating and non-encapsulated bacterium, it is non-motile although it has fimbriae, and can assume coccoid or filamentous forms (pleomorphic). Its optimum growth temperature is 37°C. This pathogen has two biovars: ovis, which usually affects small ruminants and causes caseous lymphadenitis, and biovar equi, more common in equines, bovines, camelids and bubalines, causing ulcerative lymphangitis. Its infection can lead to carcass condemnation and reduction in wool production (in ovines and caprines), milk production and meat production and, consequently, economic losses for the agricultural industry worldwide. Currently there is no effective vaccine against those illnesses. To obtain a better understanding of these species biologically, the main objective of this work is to analyze, using comparative genomics, the strain C. pseudotuberculosis 226 biovar ovis, isolated from a caprine in California, comparing it to other strains from biovars ovis and equi. The synteny analysis revealed highly conserved gene order between strain 226 and other biovar ovis strains. Phylogenomic analyses showed that the strains I19 and 267 are, respectively, the closest and the more distant phylogenetically from strain 226. Among biovar equi strains, the one with the greater phylogenomic proximity to strain 226 was strain 1/06-A. Eight pathogenicity islands were predicted, with C. pseudotuberculosis best characterized virulence genes in literature being present in island 1. No new regions related to virulence genes could be found compared to other strains. 248 orthologous genes could be found between strains I19, 267 and 226, while 282 orthologous genes could be found between strains 258, 1/06-A and 226. Based in this study it is possible to assume that strains from biovar ovis have a little varied gene repertory and strains from biovar equi have less genes shared with strain 226, reinforcing the genetic diversity between these biovars.